2014
DOI: 10.6007/ijarbss/v4-i4/751
|View full text |Cite
|
Sign up to set email alerts
|

Are Soft skills Important in the Workplace? – A Preliminary Investigation in Malaysia

Abstract: Soft skills are described as career traits that employees should possess, such as leadership skills, communication skills, a positive work attitude and teamwork. In the twenty-first century workforce, soft skills are critical in the business sector. In Malaysia, the general sentiment of employers is that graduates fail to meet the market expectation and hence are lagging behind. This has become a grave concern as Malaysian graduates are seen as lacking in soft skills. The soft skill gap is said to have caused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 18 publications
(12 reference statements)
0
37
0
5
Order By: Relevance
“…Hanapi and Nordin, 2014;Rahmat, Ayub and Buntat, (2016) argue that Malaysia faces an acute graduate unemployment problem not because of limited employment opportunities, but mainly because of graduates who are not work-ready. Graduate employability research in Malaysia is mainly tuned to identifying employability skills rather than a holistic study that explores other causal factors (Seetha, 2014;Tan et al, 2017). According to Nesaratnam and Gayen (2018), the concept of employability in literature has thus far been ambiguous and contentious without a single definitive description.…”
Section: Introductionmentioning
confidence: 99%
“…Hanapi and Nordin, 2014;Rahmat, Ayub and Buntat, (2016) argue that Malaysia faces an acute graduate unemployment problem not because of limited employment opportunities, but mainly because of graduates who are not work-ready. Graduate employability research in Malaysia is mainly tuned to identifying employability skills rather than a holistic study that explores other causal factors (Seetha, 2014;Tan et al, 2017). According to Nesaratnam and Gayen (2018), the concept of employability in literature has thus far been ambiguous and contentious without a single definitive description.…”
Section: Introductionmentioning
confidence: 99%
“…Higher learning institutions have been challenged to increase the employability of their graduates by providing the right technical skills, soft skills and work ethics (1). In line with that statement, majority of employers suggested that the curriculum in higher learning institutions must be enhanced to equip and create industry preferred and relevant graduates (2). As a matter of fact, Malaysian government has realized about this rising issue even earlier.…”
Section: Introductionmentioning
confidence: 90%
“…This indicates a connection between employees" soft skills and performance. A study on the importance of soft skills in the workplace found that the soft skills gap caused the high unemployment statistic of graduates Seetha (2014). Soft skills played an important role in determining the success of a project or work performance, and they are required for the success of the organization.…”
Section: Soft Side Of Leadership In Educationmentioning
confidence: 99%